Penolakan Permohonan Asal-Usul Anak dari Pasangan Nikah Siri - Abdul Hakam Sholahuddin; Ridho Tiar Prawira; Erifendi Churniawan (Universitas Islam Balitar, Blitar, 2023)
Abstract Clarity of legal status due to marriage between husband and wife is an essential thing in life as Indonesian citizens. Marital status must be authentically and legally proven. In addition, marriage in Indonesia adheres to the principle of monogamy. This means that a man can only have a wife and a woman can only have a husband. On the other hand, clarity of status through authentic evidence of marriage will be the legal basis for clarity of child status and clarity of status of the married couple. Based on the above theory, this study aims to (a) examine the decision given by the Judge at the Blitar Religious Court in the case of Case Number: 0039/ Pdt.P/2022/PA.BL dated January 12, 2022 regarding the Rejection of the Application for the Origin of a Child resulting from Polygamy Siri marriage / unregistered polygamy and, (b) reviewing the implications of the decision on the position of the child after the decision. The research approach used is normative legal research. Keywords: C, Siri Marriage, Marriage